2008
DOI: 10.3957/0379-4369-38.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Translocation stress and faecal glucocorticoid metabolite levels in free-ranging African savanna elephants

Abstract: There are local populations of African elephants (Loxodonta africana) which have increased to levels where they are implicated in altering vegetation types. The local reduction of elephant numbers for wildlife management objectives can involve contraception, killing excess animals, or translocation to alternative habitats. The effects these management decisions can have on the physiological stress response of free-ranging African savanna elephants are still not fully understood. We examined the effect of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 24 publications
1
34
1
Order By: Relevance
“…By comparison, an intramuscular injection of adrenocorticotropic hormone (ACTH) caused a 3-4 fold elevation of faecal GCM concentrations in an African elephant bull (Ganswindt et al 2003). Furthermore, translocation as a putative stressful event resulted in 4-5 fold increases in faecal GCM concentrations in elephants (Laws et al 2007, Viljoen et al 2008a, whereas fatal injuries detected in wild African elephants produced 5-10 fold elevations in adrenal glucocorticoid output (Ganswindt et al 2005b). The changes in GCM concentrations described in these various studies are at least partly comparable with the results of our study, underlining the importance of foot injuries in elephants as potential stressors.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, an intramuscular injection of adrenocorticotropic hormone (ACTH) caused a 3-4 fold elevation of faecal GCM concentrations in an African elephant bull (Ganswindt et al 2003). Furthermore, translocation as a putative stressful event resulted in 4-5 fold increases in faecal GCM concentrations in elephants (Laws et al 2007, Viljoen et al 2008a, whereas fatal injuries detected in wild African elephants produced 5-10 fold elevations in adrenal glucocorticoid output (Ganswindt et al 2005b). The changes in GCM concentrations described in these various studies are at least partly comparable with the results of our study, underlining the importance of foot injuries in elephants as potential stressors.…”
Section: Discussionmentioning
confidence: 99%
“…During the first month after arrival, Andile, Chova, and Moya (5 samples/animal) showed FGM levels between 0.86 and 2.24 g/g DM (individual mean values of 1.45, 1.31, and 1.80 g/g DM, respectively), which corresponds to an elevation of 47%-285% when compared with the overall mean FGM baseline value of the 12 abovementioned elephants (0.58 g/g DM). The revealed hormone values for Andile, Chova, and Moya indicate that translocation and the subsequent adaptation to a new environment resulted in an increase in FGM concentrations similar to those observed for elephants translocated within Kruger Park (Viljoen et al 2008). …”
Section: Captive Elephantsmentioning
confidence: 78%
“…Approximately 0.05 g of the fecal powder was then extracted with 80% ethanol in water (3 mL) (Ganswindt et al 2010b). The resulting extracts were measured for immunoreactive FGM using an enzyme immunoassay detecting FGMs with a 5␤-3␣-ol-11-one structure (Möstl et al 2002), which have been shown to reliably reflect adrenocortical function in African elephants (Ganswindt et al 2003;Viljoen et al 2008). Crossreactivities of the antibody used are described in Möstl et al (2002).…”
Section: Fecal Glucocorticoid Metabolite Levels In Captive Elephantsmentioning
confidence: 99%
“…It does not yet seem clear whether urine or feces is the main route for cortisol metabolite excretion in elephants, nor whether this varies between sexes. Biological validation of fecal assay techniques in wild elephants includes the increase of cortisol metabolites with natural stressors like being a subordinate herd member, being exposed to severe dry seasons, experiencing a thunder storm, or being injured [Wasser et al, 2000;Foley et al, 2001;Ganswindt et al, 2005;Millspaugh et al, 2007], and with anthropogenic stressors like being hunted [Burke et al, 2008] or translocated [e.g., Viljoen et al, 2008]. Fecal cortisol metabolite levels also co-varied with submissive behavior in one study of zoo elephants [Burks et al, 2004].…”
Section: The Hypothalamic-pituitary Adrenal Axis I: Corticosteroid Lementioning
confidence: 99%